HUBUNGAN ANTARA SIKAP DAN PENGHARGAAN TERHADAP KEPATUHAN PEKERJA DALAM PENGISIAN (HAZARD OBSERVATION CARD) DI SALAH SATU PERUSAHAAN PENYIMPANAN BAHAN KIMIA DI KALIMANTAN TIMUR - Ria Purnama Sari; Dina Lusiana Setyowati; Riza Hayati Ifroh (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2020)
HUBUNGAN ANTARA SIKAP DAN PENGHARGAAN TERHADAP KEPATUHAN PEKERJA DALAM PENGISIAN (HAZARD OBSERVATION CARD) DI SALAH SATU PERUSAHAAN PENYIMPANAN BAHAN KIMIA DI KALIMANTAN TIMUR Ria Purnama Sari Departemen Keselamatan dan Kesehatan Kerja, Fakultas Kesehatan Masyarakat Universitas Mulawarman, Samarinda Kalimantan Timur Email : riapurnamasari17584@gmail.com ABSTRACT Work accidents could occur due to unsafe working conditions and unsafe work behavior. Reporting dangerous events and accidents is a method and procedure that can be done to prevent dangerous events or accidents that recur. Bird's theory states that recurring nearmiss is mostly caused by unsafe behavior that can increase the risk of work accidents. Identification of unsafe behavior can be done with the Behavior Base Safety (BBS) approach, namely through the filling of hazard observation cards. This type of research used quantitative methods with cross sectional design. The number of samples studied was 76 workers with total sampling from workforce population. The study was conducted in July - August 2019. Data analysis in this study used the Spearman Rank test with a value of (α = 0,05). The results showed there were a relationship between attitude variables (Pvalue = 0,013) and awardin (Pvalue = 0,016. It is suggested to improve system of reward in order to increase worker motivation, make safety instructions regarding the obligation to fill a hazard reporting card, discussion forums or meetings related to the STOP Card program, design a interesting safety media communications focused on observing safe and unsafe condition in the work place. Keywords : Hazard Observation Card, Behavior Based Safety